Farmers' Resilience to Climate Change through Sustainable Agricultural Practices - Kamakaula, Yohanes; Fenetiruma, Obadja Andris (West Science Nature and Technology, 2025)
Rice farmers in Indonesia face significant challenges due to climate change, including unpredictable weather patterns, extended dry spells, and increased pest outbreaks. This study explores the resilience of rice farmers to climate change through sustainable agricultural practices using a qualitative approach with five purposively selected participants. Data collection included semi-structured interviews, field observations, and document reviews, analyzed through thematic analysis. Results reveal that farmers are adopting practices such as integrated pest management, organic fertilizers, efficient water use, and resilient seed varieties. However, barriers such as economic constraints, knowledge gaps, and inconsistent institutional support hinder broader adoption. The findings emphasize the need for targeted policy interventions, capacity-building programs, and leveraging community networks to enhance resilience. This study contributes to understanding how grassroots-level adaptations can mitigate climate impacts and promote agricultural sustainability in Indonesia.